Social support and user engagement with task-shared psychological treatments in the real world: Findings from the PRIME India study - Saloni Dev; John Griffith; Vikram Patel; Alisa Lincoln (Elsevier, 2023)
Purpose: Task sharing in psychological treatments has been recognized as an effective strategy for bridging the global mental health treatment gap. However, more research is needed to better support its implementation in routine care. Mental health services users' engagement with treatment is a crucial implementation factor, yet empirical evidence on its determinants remains sparse. The current study aims to investigate social support as a predictor of users' session attendance, a key indicator of treatment engagement, within a task-shared psychological treatment. Methods: This is a secondary analysis of cohort study data from the Program for Improving Mental Health Care (PRIME) implemented in Sehore district, India, where trained non-specialist health workers delivered manualized treatment for depression and alcohol use disorder (AUD; n = 240 in depression cohort, n = 190 in AUD cohort). Quasi-Poisson regression models were used to assess the association between users' perceived social support at baseline and treatment session attendance at 3-month follow-up, controlling for socio-demographic and clinical characteristics. Result: Within the depression cohort, a 4-point increase in social support score at baseline predicted a higher number of treatment sessions attended by 3-month follow up (IRR = 1.44, 95% CI: 1.06, 1.93). Within the AUD cohort, we noted insufficient statistical evidence for a weak association between users' social support and the number of treatment sessions attended in adjusted analysis (IRR = 1.02; 95% CI: 0.69, 1.49). Conclusion: Our findings suggest that the implementation of task-shared psychological treatments for depression into routine care may be enhanced by strategies that activate or build upon the functional roles of users' social support.